Camera Trap Records of Sumatran Striped Rabbits (Nesolagus netscheri) in Batutegi Protection Forest, Lampung, Indonesia. - Huda, Robithotul; Subagio, Aris; Sanchez, Karmele Llano; Moore, Richard; Aryanto, Dikki (Media Konservasi, 2024)
The Sumatran striped rabbit (Nesolagus netscheri) is a little-known lagomorph endemic to southwest Sumatra. Despite its taxonomic significance, limited sightings and a paucity of ecological data have hindered population assessments and conservation efforts. This study presents findings from camera trap surveys conducted in Batutegi Protection Forest (BPF), Lampung Province, Indonesia. The BPF, covering approximately 58,000 hectares, hosts diverse flora and fauna but faces threats from habitat loss and due to agricultural encroachment. The study was carried out in Way Sekampung and Rindingan Forests within BPF. Camera trapping between 2017 and 2023 yielded 42 independent photographs of solitary individuals. The majority of sightings were at elevations above 600m, but two occurred at 366 and 454 m. The rabbits exhibited nocturnal behavior, with peak activity observed between 19:00 and 21:00 and 02:00 and 03:00. Our sightings from BPF, which is situated at some distance from the Bukit Barisan Selatan National Park, provide new records of small but isolated populations of Sumatran striped rabbits in fragmented pockets of remnant forest. Conservation efforts by the Forest Management Unit (KPH) are underway in BPF, but further measures are necessary to preserve the forests rich biodveristy. This study emphasizes the need for continued monitoring and conservation efforts to protect the Sumatran striped rabbit and its habitat. Further research is warranted to assess population densities and ecological requirements, underscoring the importance of implementing effective and collaborative conservation measures in the region.